Deciphering Underlying Drivers of Disease Suppressiveness Against Pathogenic Fusarium oxysporum - Ou, Yannan; Penton, C. Ryan; Geisen, Stefan; Shen, Zongzhuan; Sun, Yifei; Lv, Nana; Wang, Beibei; Ruan, Yunze; Xiong, Wu; Li, Rong; Shen, Qirong (Frontiers in Microbiology, 2019)
Soil-borne diseases, especially those caused by fungal pathogens, lead to profound annual yield losses. One key example for such a disease is Fusarium wilt disease in banana. In some soils, plants do not show disease symptoms, even if the disease-causing pathogens are present. However, the underlying agents that make soils suppressive against Fusarium wilt remain elusive. In this study, we aimed to determine the underlying microbial agents governing soil disease-suppressiveness. We traced the shift of microbiomes during the invasion of disease-causing Fusarium oxysporum f. sp. cubense in disease-suppressive and disease-conducive soils. We found distinct microbiome structures in the suppressive and conducive soils after pathogen invasion. The alpha diversity indices increased (or did not significantly change) and decreased, respectively, in the suppressive and conducive soils, indicating that the shift pattern of the microbiome with pathogen invasion was notably different between the suppressive and conductive soils. Microbiome networks were more complex with higher numbers of links and revealed more negative links, especially between bacterial taxa and the disease-causing Fusarium, in suppressive soils than in conducive soils. We identified the bacterial genera Chryseolinea, Terrimonas and Ohtaekwangia as key groups that likely confer suppressiveness against disease-causing Fusarium. Overall, our study provides the first insights into agents potentially underlying the disease suppressiveness of soils against Fusarium wilt pathogen invasion. The results of this study may help to guide efforts for targeted cultivation and application of these potential biocontrol agents, which might lead to the development of effective biocontrol agents against Fusarium wilt disease.